CO2 carbonation-induced improvement in strength and microstructure of reactive MgO-CaO-fly ash-solidified soils. (30th December 2019) - Wang, Dongxing; Zhu, Jiaye; He, Fujin
Highlights: Carbonation coupled with industrial waste is an innovative solidification technique. Carbonation improves strength & microstructure of MgO-CaO-fly ash solidified soil. Water content, binder amount, mass ratio & elapsed time control carbonation effect. Mg- and Ca-carbonates are intrinsic mechanisms for densification and cementation. CO2 emission of MgO-CaO-fly ash blend is reduced by 38.8–64.7% in contrast to PC. Abstract: An innovative approach combining CO2 accelerated carbonation with industrial by-products is systematically investigated to produce low-carbon and sustainable cementing materials, in which reactive MgO-CaO-FA (fly ash) blends are introduced to replace traditional Portland Cement (PC) with high energy consumption, mineral resources demand and CO2 emissions. The effect of initial water content, carbonation time, binder amount and mass ratio of MgO/CaO on the mechanical and microstructural properties of carbonated solidified soils is analyzed through unconfined compressive strength (UCS), scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests. The carbonation efficiency and carbon footprint of cementitious materials are evaluated under different schemes. The test results indicate that CO2 carbonation combined with reactive MgO-CaO-FA blends is proved highly effective and reliable to improve the strength performance of soil samples. The compressive strength of carbonated soils increases with binder content and mass ratio of MgO/CaO, which is related to the densification of pore system by carbonation products. An optimum UCS is reached at 6 h of carbonation, followed by a plateau or an important decrease with carbonation time. Water content controls the diffusion and permeability rate of CO2, affecting the chemical contact between Ca 2+ /Mg 2+ released from MgO-CaO-FA blend and dissolved CO2 and further the strength of carbonated samples. XRD and SEM results demonstrate that the strength gain is mainly attributed to the formation of carbonation products (CaCO3, MgCO3 ), facilitating the densification and cementation of solidified materials. High-Ca FA promotes the carbonation efficiency by reducing porosity and providing nucleation sites for carbonate precipitation, while reactive MgO plays a more important role than CaO in developing binding capacity and building skeleton structure. The carbon footprint analysis reveals that compared with PC, the net CO2 emissions of MgO-CaO-FA blends are effectively reduced by 38.8–64.7%. The coupling technique of CO2 carbonation with industrial by-products is proved a feasible alternative to traditional PC in soil solidification.